12v = 18+6v
move +6v to the other side
sign changes from +6v to -6v
12v-6v= 18+6v-6v
12v-6v= 18
6v= 18
divide by 6 to get v by itself
6v/6=18/6
Answer:
v= 3
Answer:
I'll choose the first one but don't know the right one
Answer:
The answer to your question is: (3x + 5)(9x² - 15x + 25)
Step-by-step explanation:
Data
G(x) = 27x³ + 125
This is a sum of cubes
Process
![\sqrt[3]{27} = 3](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B27%7D%20%3D%203)
![\sqrt[3]{125} = 5](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B125%7D%20%3D%205)
27x³ + 125 = (3x)³ + (5)³ = (3x + 5)(9x² - 15x + 25)
I think -23/4 hope it helps
The first one hopes this helps